Shared decision making: why the slow progress? An essay by Neal Maskrey. (5th December 2019) - Maskrey, Neal
Abstract : After more than 40 years of research and policy endorsement, adoption of shared decision making into routine practice has been remarkably slow. Neal Maskrey blames a lack of focus on doctors' broader communication skills